The comparison of the population rhinoceros beetle (Oryctes rhinoceros) in immature oil palm at replanting area and new open area, Ladang Fima Cendana, Terengganu / Muhammad Zul Adam Mohd Razak - Mohd Razak, Muhammad Zul Adam (Faculty of Plantation and Agrotechnology, 2018)
Oil palm or its scientific name Eleais guineensis is one of the major crops in Malaysia that give high profit to country and largely contribute more to the Malaysia economy development. However there are various obstacles like pest and disease that limits the production of oil palm. Oryctes rhinoceros commonly known as the rhinoceros beetle is one of the dominant destructive pest that known to inflict serious damage on immature oil palm trees and cause significant yield loss of oil palm. Oryctes rhinoceros will readily migrate and infest an area of oil palm once new open area or replanting has conducted. This study focuses on the population of the beetle at Ladang Fima Cendana, Kemaman, Terengganu. The aggregation pheromone (ethyl-4-methyloctonoate) has been used during this study where it functions for mass trapping and monitoring beetles population. Pheromone trap was placed about 1 trap for every 5 hectares in immature oil palm for each area. The result obtained shows that there is no difference in result population of beetles in immature palm for both area (P > 0.05).